2014
DOI: 10.1038/bjc.2014.207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of FLT-PET-CT as an imaging biomarker of proliferation in primary breast cancer

Abstract: Background:[18F]fluorothymidine (FLT) has been proposed as a positron emission tomography (PET)-imaging biomarker of proliferation for breast cancer. The aim of this prospective study was to assess the feasibility of FLT-PET-CT as a technique for predicting the response to neoadjuvant chemotherapy (NAC) in primary breast cancer and to compare baseline FLT with Ki-67.Methods:Twenty women with primary breast cancer had a baseline FLT-PET-CT scan that was repeated before the second cycle of chemotherapy. Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Small, single-center preliminary studies indicated good predictive value for response (1114), whereas others did not (12,1517). Our multicenter study suggested some utility for 18 F-FLT as an early predictor of response, but preliminary reports of other multicenter trials did not find a predictive value for 18 F-FLT (25).…”
Section: Discussionmentioning
confidence: 96%
“…Small, single-center preliminary studies indicated good predictive value for response (1114), whereas others did not (12,1517). Our multicenter study suggested some utility for 18 F-FLT as an early predictor of response, but preliminary reports of other multicenter trials did not find a predictive value for 18 F-FLT (25).…”
Section: Discussionmentioning
confidence: 96%
“…In the neoadjuvant setting, the few studies are contradictory. A recent study including 20 women has reported disappointing results: FLT breast tumor uptake at [95]. In contrast, preliminary results of the ACRIN 6688 multicentric trials, presented at the 2014 ASCO meeting, found that FLT-PET after the first cycle of NAC was marginally predictive of pCR in 51 women [96].…”
Section: Changes In Tumor Cell Proliferationmentioning
confidence: 99%
“…Correlation with immunohistochemistry measures of proliferation such as Ki-67 has been shown for several tumor types including breast cancer (18)(19)(20). The limitations of 18 F-FLT PET are in imaging the liver and the bone marrow because 18 F-FLT undergoes glucuronidation in the liver, leading to a high background uptake level, and in the bone marrow there is high uptake of 18 F-FLT, which is attributed to physiologic proliferation.…”
Section: Breast Cancer Proliferation Probesmentioning
confidence: 99%